PENERAPAN AROMATERAPI MAWAR TERHADAP PENGURANGAN RASA NYERI PERSALINAN PADA NY P DI PUSKESMAS TANJUNG BALAI KARIMUN: PENERAPAN AROMATERAPI MAWAR TERHADAP PENGURANGAN RASA NYERI PERSALINAN PADA NY P DI PUSKESMAS TANJUNG BALAI KARIMUN - Maryati, Maryati; Utami, Risqi; Fahnawal, T. Marzila (Universitas Batam, 2024)
Labor pain needs to get good treatment and not cause complications that can interfere with labor. Aromatherapy is a complementary therapy that is able to treat pain and infection because it is an analgesic, anti-inflammatory and antimicrobial (Muchtaridi, 2015). Objective To provide midwifery care to mothers giving birth on an ongoing basis, with management of midwifery care in accordance with midwifery service standards. Midwifery care that is applied is the application of rose aromatherapy to reduce labor pain. Methods The type of research used in the preparation of the practice report was a descriptive study, conducted at the Tanjung Balai Karimun Health Center in March 2023. The results of midwifery care related to the application of rose aromatherapy to midwifery care for mothers in labor to reduce labor pain have been carried out Conclusion Evaluation of the care provided shows that giving rose aromatherapy can help reduce pain in labor